Nilai Perjuangan Pada Novel Sekali Peristiwa Di Banten Selatan Karya Pramoedya Ananta Toer: Kajian Sosiologi Sastra - Putri Cahyani (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This study aims to (1) analyze the intrinsic elements contained in Pramoedya Ananta Toer novel once an event in south Banten, (2) describe the values of struggle contained in Sekali peristiwa di Banten Selatan by Pramoedya Ananta Toer. Qualitative method is the used this research. Because this qualitative method examines things related to society, behavior, history, and so on, and this research relates to society. Then the approach used is the sociology of literature approach, and the data source for this research is the novel Sekali Peristiwa di Banten Selatan by Pramoedya Ananta Tier; then values of struggle, contained in this novel, namely, the first is the value of courage, the second is the value of the spirit of unity, and the third is the value of cooperatuib. These values are all part of struggle, can be implemented in everyday life. Because deep life does not escape from the name of struggle, and most important of all is the spirit of unity, because if there no spirit of unity, there will be none other values.